NIZHNI NOVGOROD EXPERIENCE OF HISTORICALPMILITARY RECONSTRUCTION - Dmitry A. Nikolaev (Высшее образование в России)
The article touches upon a phenomenon of military historical reconstruction as an actual and demanded form of study of military history. Concrete practices of its embodiment are described.